Digital Transformation and Understanding the Impact on Construction Project Management in Iraq - Abbas Abdulameer Khalaf (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The construction sector is currently undergoing significant changes as a result of the adoption of digitaltechnologies. The utilisation of Building Information Modelling (BIM) has garnered considerable interest in recentyears from scholars and industry experts. The sector has seen major changes as a result of its rising success. Giventhese changes, the traditional knowledge and skills possessed by project specialists or managers seem insufficientin properly supervising the new information component of construction project management. As projects advance,the inclusion of new roles such as BIM managers, BIM coordinators, BIM modellers, and information managers isbecoming crucial to meet the demand for enhanced capabilities. Multiple studies have analysed these novel rolesfrom a theoretical perspective, but have not investigated their correlation with conventional roles in projectmanagement, nor have they explored how project managers and BIM specialists position themselves in relation tothe overall processes outlined in the BIM implementation guides. This case study illustrates that the duties of BIMspecialists varied among various fields and go beyond solely technical assignments. Moreover, the informationsub-process predominantly focuses on BIM managers, leading to the establishment of two distinct sources ofleadership within a project: BIM managers and project managers. According to the poll, professionals believe thatthe BIM collaboration methods described in the BIM implementation plan and project documents are too general.Moreover, there is always a difference between specified methods and the ones actually used in the project.